2022
DOI: 10.5194/acp-22-14177-2022
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability of tropospheric ozone and ozone profiles in the Korean Peninsula during the East Asian summer monsoon: insights from multiple measurements and reanalysis datasets

Abstract: Abstract. We investigate the temporal variations of ground-level ozone and balloon-based ozone profiles at Pohang (36.02∘ N, 129.23∘ E) in the Korean Peninsula. Satellite measurements and chemical reanalysis products are also intercompared to address their capability of providing consistent information on the temporal and vertical variability of atmospheric ozone. Sub-seasonal variations of the summertime lower-tropospheric ozone exhibit a bimodal pattern related to atmospheric weather patterns modulated by th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In the UTLS, ECHAM-CTL shows underestimation while ERA5, CAMS, and MERRA2 show overestimation compared to ozonesondes. The ozone profiles at Pohang (36.02°N, 129.23°E) in the Korean Peninsula, in comparison with reanalysis products (MERRA2 and CAMS), also show largely overestimation (by 150 ppb) in the troposphere and stratosphere 40 .
Figure 3 The peak value of ozone mixing ratio from PDF curve at different pressure levels ozonesonde (black), ERA5 (red), CAMS (blue), MERRA2 (cyan), and ECHAM–CTL (green).
…”
Section: Comparison Of Ozonesondes With Reanalysis and Echam6-hammoz ...mentioning
confidence: 91%
“…In the UTLS, ECHAM-CTL shows underestimation while ERA5, CAMS, and MERRA2 show overestimation compared to ozonesondes. The ozone profiles at Pohang (36.02°N, 129.23°E) in the Korean Peninsula, in comparison with reanalysis products (MERRA2 and CAMS), also show largely overestimation (by 150 ppb) in the troposphere and stratosphere 40 .
Figure 3 The peak value of ozone mixing ratio from PDF curve at different pressure levels ozonesonde (black), ERA5 (red), CAMS (blue), MERRA2 (cyan), and ECHAM–CTL (green).
…”
Section: Comparison Of Ozonesondes With Reanalysis and Echam6-hammoz ...mentioning
confidence: 91%
“…In the UTLS, ECHAM-CTL shows underestimation while ERA5, CAMS, and MERRA2 show overestimation compared to ozonesondes. The ozone pro les at Pohang (36.02 o N, 129.23 o E) in the Korean Peninsula, in comparison with reanalysis products (MERRA2 and CAMS), also show largely overestimation (by 150 ppb) in the troposphere and stratosphere 34 .…”
Section: Probability Density Function (Pdf) Analysismentioning
confidence: 93%
“…Further, we show a comparison of all data sets for the special case on 15th August 2016, when there was no ATAL observed over Nainital in the UTLS region 34,35 . The ozone pro le on this day shows a sharp, deep low ozone concentration near 140 to 100 hPa (363-380 K).…”
Section: Comparison Of Ozone Pro Les On a Special Case Day 15 August ...mentioning
confidence: 99%
“…It has a swath width of 2600 km and provides a spatial resolution of 13 km × 24 km. OMI can complete a global scan in just one day, measuring column concentrations and profiles of O 3 , NO 2 , SO 2 , as well as data on aerosols, clouds, surface ultraviolet radiation, and various other parameters 18 , 44 . Previous studies have shown that the OMI ozone column concentrations and profile data exhibit a reasonable consistency with lower- to mid-troposphere ozone across the world 17 , 45 .…”
Section: Methodsmentioning
confidence: 99%